RANCANG BANGUN MAGNETIC SOLENOID DOOR LOCK DENGAN SPEECH RECOGNITION MENGGUNAKAN NODEMCU BERBASIS ANDROID - Sayed Achmady; Laila Qadriah; Abthal Auzan (Jurnal Real Riset, 2022)
Door locks are one of the most important requirements for today's security systems and provide  privacy  for  a  room  with  a  specific  purpose.  Therefore,  Speech  Recognition technology is needed as a substitute for conventional keys to make it more practical. This research  is  to  design  a  magnetic Solenoid  door  lock  with  Speech  Recognition  using  an Android-based NodeMCU ESP8266 which can make it easier for humans to open door locks and close door locks easily just by opening the application and saying Voice commands. NodeMCU ESP8266 is the main controller for controlling the door when the command is spoken in the Voice Control application which is connected to the android smartphone as a controller for opening the door lock and closing the door lock. The design of this Door Control tool uses the main components, namely NodeMCU ESP8266, Magnetic Solenoid door lock, Relay Module, Power Adapter. While the supporting components are Breadboard, IC 7805, DC Power Jack, Jumper Cable. Speech Recognition application on Android smartphones as a control system to unlock doors and close door locks remotely or close. This application aims as a control tool to open the door lock and close the door lock with Voice commands. This tool can make it easier for users to open door locks and close door locks online.Keywords : Door Lock, NodeMCU, Magnetic Solenoid, Speech Recognition, Android